Creation of a Family Medicinal Plant Garden in the Community Service Program in Badama Region, Cimalaka Village, Sumedang - Muhammad Panji Abdurrahman; Nesywa Nur Aini; Hanadia Rahmani Gania Putri; Fathiya Reina Maulidia; Mochamad Bintang; Hawa Aufa; Imel Aura Agustin; Habib Khirzin Al Mahdaly; Halimah, Nur; Nopiyanti Rahmawati; Nelis Hernahadini (Ikatan Dosen Menulis, 2025)
TOGA (Family Medicinal Plant) is a plant that is efficacious and is used to meet family needs for medicines. This TOGA aims to meet the community's needs for plant-derived drugs, thereby building health as a catalyst for community empowerment activities. The implementation of this service was carried out in Badama hamlet with the Real Work Lecture (KKN) scheme, to increase the community's understanding of the benefits of TOGA. In general, the people of Badama Hamlet work as farmers. In addition, this village has the potential for land development, including the cultivation of medicinal plants. The methods employed in the implementation of the service include socialization, the collection of medicinal plants, and the creation of a TOGA garden. The result of this activity is a TOGA garden that the community can use for medicinal needs.